Immunomodulatory Effects of Gold Nanoparticles: Impacts on Immune Cells and Mechanisms of Action - Khadijeh Koushki; Prapannajeet Biswal; Geraldine Vidhya Vijay; Mahvash Sadeghi; Sajad Dehnavi; Ngoc Tuyet Tra; Sai Kumar Samala; Mahdieh Yousefi Taba; Arjun Balaji Vasan; Emily Han; Yuri Mackeyev; Sunil Krishnan (Nanomaterials)
Traditional anti-inflammatory medications—such as corticosteroids, biological agents, and non-steroidal anti-inflammatory drugs—are commonly employed to mitigate inflammation, despite their potential for debilitating side effects. There is a growing need for alternative next-generation therapies for symptomatic, unchecked, and/or detrimental inflammation with more favorable adverse effect profiles. The long history of use of gold salts as anti-inflammatory agents and the more recent exploration of gold nanoparticle (AuNP) formulations for clinical indications suggest that the targeted delivery of nanoparticles to inflammatory sites may be a promising approach worth investigating. Coupled with peptides that specifically target immune cells, AuNPs could potently counteract inflammation. Here, we provide an overview of the selective infiltration of AuNPs into immune cells and summarize their interactions with and impact on these cells. Additionally, we provide a comprehensive mechanistic summary of how AuNPs exert their anti-inflammatory effects.